Leukemia relapse following unmanipulated haploidentical transplantation: a risk factor analysis on behalf of the ALWP of the EBMT - Simona Piemontese; Ariane Boumendil; Myriam Labopin; Christoph Schmid; Fabio Ciceri; William Arcese; Yener Koc; Zafar Gulbas; Johanna Tischer; Benedetto Bruno; Depei Wu; Didier Blaise; et al. (Journal of Hematology & Oncology, 2019)
Abstract Background As information on incidence, risk factors, and outcome of acute leukemia (AL) relapse after unmanipulated haploidentical stem cell transplantation (haplo-SCT) is scarce, a retrospective registry study was performed by the Acute Leukemia Working Party of the European Society for Blood and Marrow Transplantation. Methods Among 1652 transplants performed for lymphoblastic and myeloid AL between 2007 and 2014, 587 patients (acute lymphoblastic leukemia (ALL) 131, acute myeloid leukemia (AML) 456) with detailed information were analyzed aiming to identify risk factors for post-transplant relapse and for overall survival (OS) after relapse. Results The cumulative incidence of relapse at 3 years was 44% (35–53%) for ALL and 32% (27–36%) for AML (p = 0.023). In ALL, risk factors for relapse were disease status different from the first complete remission (CR1) at haplo-SCT (CR2 vs CR1: HR 2.85, p = 0.011; advanced vs CR1: HR 14.28, p < 0.0001) and male donor gender (HR 3.64, p = 0.0002), while in AML, risk factors were advanced disease at haplo-SCT (advanced vs CR1: HR 3.95, p < 0.0001) and comorbidities (HCT-CI) ≥ 3 (HR 1.75, p = 0.014). Transplants performed in more recent years were associated with lower relapse incidence (RI) in AML, but not in ALL (HR 0.91, p = 0.042). After relapse, median follow-up was 13 months (mos). OS at 1-year post relapse was 18%. Prognostic factors for superior OS after relapse were remission at time of haplo-SCT (CR vs advanced: HR 0.71, p = 0.028), time from transplant to relapse (≥ 5 mos vs < 5 mos: HR 0.530, p < 0.0001), and bone marrow as a stem cell source (peripheral blood (PB) vs bone marrow (BM): HR 1.473, p = 0.016). Conclusions Risk factors for relapse after haploidentical transplantation were disease specific. Longer OS after relapse was achieved in particular by patients both in CR at haplo-SCT and relapsing more than 5 months after transplant (1-year OS 33%).